2016
DOI: 10.1371/journal.pone.0156297
|View full text |Cite
|
Sign up to set email alerts
|

Potential Role of Vegetarianism on Nutritional and Cardiovascular Status in Taiwanese Dialysis Patients: A Case-Control Study

Abstract: Background & ObjectivesCardiovascular disease remains the most common cause of death for patients on chronic dialysis. End stage renal disease patients undergoing dialysis imposed to reduce phosphorus intake, which likely contributes to development of vegetarian diet behaviors. Vegetarian diets are often lower in protein content, in contradiction to the recommendation that a high protein diet is followed by patients undergoing dialysis. The purpose of the study was to investigate the effects of a vegetarian di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Main characteristics of the included 21 studies are summarized in Table 1 . Studies were conducted across 3 continents, most studies were conducted in Asia (12 studies 19 , 22 27 , 29 , 32 , 35 , 36 ), followed by Europe (6 studies 18 , 20 , 21 , 28 , 30 , 37 ) and South America (3 studies 17 , 33 , 34 ). All studies, with exception of one prospective study 29 , used a cross-sectional design.…”
Section: Resultsmentioning
confidence: 99%
“…Main characteristics of the included 21 studies are summarized in Table 1 . Studies were conducted across 3 continents, most studies were conducted in Asia (12 studies 19 , 22 27 , 29 , 32 , 35 , 36 ), followed by Europe (6 studies 18 , 20 , 21 , 28 , 30 , 37 ) and South America (3 studies 17 , 33 , 34 ). All studies, with exception of one prospective study 29 , used a cross-sectional design.…”
Section: Resultsmentioning
confidence: 99%
“…While various markers of overnutrition, such as increased body mass index or high serum cholesterol levels, have shown deleterious effects upon cardiovascular disease and death in the general population, multiple observational studies have paradoxically shown survival benefit in dialysis patients [ 46 , 47 ]. Notably, in a Taiwanese study of 21 vegetarian dialysis patients and 42 age- and sex-matched non-vegetarian dialysis patients selected as controls, those who followed vegetarian diets demonstrated markers of subclinical protein malnutrition and vitamin D deficiency [ 48 ]. Indeed, monitored liberalization of protein intake is needed to ensure adequate dietary intake and prevention of PEW in diabetic ESRD patients receiving dialysis [ 49 ].…”
Section: Dietary Protein Intake In Diabetic Kidney Disease Patientmentioning
confidence: 99%
“…For example, the impact of red meat on inflammation may be influenced by bowel function, iron and phosphorus status, presence and control of anemia, diabetes and hypertension, portion size and cut of meat, preparation and cooking method, and meal pairings. Epidemiological data in this area are limited, but in a cross‐sectional analysis of HD patients in Taiwan, high‐sensitivity C‐reactive protein concentrations did not differ between vegetarians and nonvegetarians …”
Section: Dietary Strategies For Protein‐energy Wastingmentioning
confidence: 99%
“…4 Inflammation pro- Epidemiological data in this area are limited, but in a cross-sectional analysis of HD patients in Taiwan, high-sensitivity C-reactive protein concentrations did not differ between vegetarians and nonvegetarians. 42 Although metabolic derangements are important dietary determinants of appetite and intake, other dietary factors may contribute to HD patients' impaired dietary intakes. One of the key factors determining dietary intake is pleasure.…”
mentioning
confidence: 99%